Orodispersible Films-Current State of the Art, Limitations, Advances and Future Perspectives - Jan Ferlak; Weronika Guzenda; Tomasz Osmałek (MDPI AG, 2023)
Orodispersible Films (ODFs) are drug delivery systems manufactured with a wide range of methods on a big scale or for customized medicines and small-scale pharmacy. Both ODFs and their fabrication methods have certain limitations. Many pharmaceutical companies and academic research centers across the world cooperate in order to cope with these issues and also to find new formulations for a wide array of APIs what could make their work profitable for them and beneficial for patients as well. The number of pending patent applications and granted patents with their innovative approaches makes the progress in the manufacturing of ODFs unquestionable. The number of commercially available ODFs is still growing. However, some of them were discontinued and are no longer available on the markets. This review aims to summarize currently marketed ODFs and those withdrawn from sale and also provides an insight into recently published studies concerning orodispersible films, emphasizing of utilized APIs. The work also highlights the attempts of scientific communities to overcome ODF's manufacturing methods limitations.